University Consolidations and Multi-Campus Institutions: Prevailing when Cultures Collide - Jill G Schulze; Nancy Dalman; Jeanelle Morgan (Academic Chairpersons Conference Proceedings, 2016)
University consolidations have escalated since 2007. We will share our experiences of working through departmental consolidation and multi-campus challenges from our perspective as administrators located on different campuses. Following this, we will facilitate a discussion of best practices for multi-campus problem-solving and distance communication.
Keywords: Consolidation; Merger; Multi-campus; Campus culture; Decision-making